2020
DOI: 10.3389/fpsyt.2020.00479
|View full text |Cite
|
Sign up to set email alerts
|

Women Undergoing Hormonal Treatments for Infertility: A Systematic Review on Psychopathology and Newly Diagnosed Mood and Psychotic Disorders

Abstract: Background: The association between infertility treatments and mental disorders has been poorly addressed. This work aims to review current evidence on the psychopathological effects of hormonal treatments used for infertility on women and the occurrence of newly diagnosed mood and psychotic disorders.Methods: A systematic review was performed by searching PubMed and clinicaltrials.gov databases from inception until September 2019. Clinical trials on hormone treatments for infertility in patients with mood or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…These treatments can significantly interfere with work and travel schedules and are particularly inconvenient for those with a rigid work schedule or who live far away from a fertility clinic. The hormones involved with fertility treatment have emotional side effects including irritability, mood lability, tearfulness, anxiety and depression (Choi et al, 2005; González‐Rodríguez et al, 2020).…”
Section: Psychological Components Of Infertilitymentioning
confidence: 99%
“…These treatments can significantly interfere with work and travel schedules and are particularly inconvenient for those with a rigid work schedule or who live far away from a fertility clinic. The hormones involved with fertility treatment have emotional side effects including irritability, mood lability, tearfulness, anxiety and depression (Choi et al, 2005; González‐Rodríguez et al, 2020).…”
Section: Psychological Components Of Infertilitymentioning
confidence: 99%
“… 5 There have not been any studies reported in the literature about the psychiatric effects of hormone treatments to treat infertility on patients with bipolar disorder, schizophrenia, or other psychotic disorders. 5 Nevertheless, there were no other cases reported about psychiatric complications after an IVF treatment both in post‐COVID and non‐COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“… 6 For this reason, fertility treatments that trigger hypoestrogenism may have an aggravating effect on depressive or psychotic symptoms. 5 On the other hand, current data on the association between progesterone and schizophrenia are inconsistent. Some studies reveal neuroprotective properties for progesterone, while other studies reveal the destructive effects of the hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Important for health providers is the fact that psychotic episodes can be triggered or exacerbated by drugs used to treat commonly occurring comorbidities. Examples are corticosteroids for autoimmune disease [106] and agents used to treat infertility [107,108].…”
Section: Non-psychiatric Comorbiditiesmentioning
confidence: 99%